School Districts’ Assessment of the French Language Proficiency of Prospective FSL Teachers - Merchant, Stefan; Jack, David; Hermans-Nymark, Laura (Canadian Journal of Educational Administration and Policy / Revue canadienne en administration et politique de l’éducation, 2023)
It is a widespread practice among Canadian school districts to assess the French language proficiency of candidates applying for French as a Second Language (FSL) teaching positions. This pan-Canadian study used surveys, interviews, and website data to examine the French language proficiency assessment practices and processes used by Canadian schools when hiring FSL teachers. The findings show that almost 90% of Canadian school districts assess French language proficiency when hiring FSL teachers and that the most common form of assessment is to ask one to three questions in French (with candidates responding in French) during the employment interview. Evaluation of the candidates’ responses is rarely informed by a language proficiency framework or rubric; instead, evaluators’ decisions are informed by their overall impressions of the candidate’s language proficiency. Other promising assessment practices are described, along with suggestions about how districts may improve their French language proficiency assessments when hiring FSL teachers.